Rules of Engagement: Builders and Barriers to Developing and Delivering Intellectually Stimulating, Non-credit Learning Experiences Offered through the Osher Lifelong Learning Institutes on University and College Campuses in the United States - Kit Kacirek (Adult Education Research Conference, 2013)
Program administration within higher education can be especially challenging for those who are unfamiliar with academia’s bureaucratic processes and constraints. This discussion explores viable avenues for identifying the challenges that directors of non-credit adult learning programs face when associated with degree granting academic institutions.